IMPLEMENTASI KEBIJAKAN PROGRAM JARING PENGAMAN SOSIAL DALAM PENANGGULANGAN KEMISKINAN DI ERA PANDEMI COVID-19 - Herijal Putra, Nanda; Anzaikhan, M. (Fakultas Ilmu Sosial dan Ilmu Pemerintahan, 2023)
This study examines the implementation of JPS Program policies in poverty reduction in the Covid-19 Pandemic Era. The research location is in Kecamatan Nurussalam Kabupaten Aceh Timur. The approach used is a qualitative research method. The problems studied are about the implementation of the JPS Program policy in Kecamatan Nurussalam Kabupaten Aceh Timur in the context of overcoming poverty due to the Covid-19 Pandemic as well as the positive and negative impacts of implementing the JPS Program policy on the poor in Kecamatan Nurussalam Kabupaten Aceh Timur due to the Covid-19 Pandemic. The results of the study found that the Covid-19 Pandemic that occurred in Indonesia caused the poor in Kecamatan Nurussalam Kabupaten Aceh Timur to lose their jobs. In dealing with this phenomenon, the government implements the JPS Assistance Program policies is the Bantuan Langsung Tunai Dana Desa (BLT DD), Bantuan Pelaku Usaha Mikro (BPUM), Bantuan Kartu Prakerja, Subsidi Listrik dan Bantuan Sosial yaitu Bantuan Program Keluarga Harapan (PKH), Bansos Sembako dan Bantuan Sosial Tunai (BST). The implementation of the JPS Program policy in Kecamatan Nurussalam Kabupaten Aceh Timur was able to increase the purchasing power of the poor for their food needs. This reality is a positive impact of the JPS Program. Meanwhile, the negative impact of the implementation of the JPS Program policy is that the poor people in Kecamatan Nurussalam Kabupaten Aceh Timur are getting lazy to work so they are very dependent on the assistance that the government provides every month.